Root-associated microbial diversity and metabolomics in maize resistance to stalk rot - Wang, Liming; Jia, Jiao; Su, Qianfu; Cao, Hongzhe; Jia, Shiqi; Si, Helong; Cao, Zhiyan; Ma, Shujie; Xing, Jihong; Zhang, Kang; Dong, Jingao (Frontiers in Microbiology, 2024)
As one of the three major food crops in the world, maize plays a significant role in alleviating the food crisis. Maize stalk rot can reduce maize yield and mechanical harvesting efficiency. In addition, mycotoxins such as Deoxynivalenol (DON) and Zearalenone (ZEN) produced by maize stalk rot pathogens can also harm livestock and human health. Maize stalk rot is an infection of the whole growth period, and there are no effective control measures at present. Therefore, it is of great significant to study the pathogenesis and control mechanism of stalk rot from multiple perspectives. In the present study, root and rhizosphere soil of disease-resistant inbred line Y853 and disease-susceptible inbred line Q478 were collected at the dough stage (R4) and maturity stage (R6) of maize, respectively. The effects of resistant/susceptible inbred line on soil microorganisms were analyzed by amplicon sequences and metabolomics. The results showed that there was different microbial community composition from different inbred lines in different growth stages. Specifically, the abundance of Arthrobacter, Streptomyces and Bacillus in R4 rhizosphere soil was higher than that of R6, while the rhizosphere fungal composition of LR853 was significantly different from that of the other three compartments. Co-occurrence network analysis showed that the pathogen Fusarium had the highest degree centrality and closeness centrality in the DR478. Moreover, metabolomics analysis showed that four main metabolic pathways were significantly enriched, and 15 metabolites were upgrade in resistant inbred line. Furthermore, microbes, especially fungi, also were related to these 15 metabolites. Our results revealed that maize resistance to stalk rot is closely related to root-associated microbiota and rhizospheric metabolites, which would be a new perspective of phytopathogenic biocontrol.